An Overview of Early Detection of Mental Health using SRQ 20 among Hospital Health Workers - Rokhmayanti Rokhmayanti; Widea Rossi Desvita; Siti Kurnia Widi Hastuti; Fardhiasih Dwi Astuti; Rena Anjeli Wibowo; Pradisa Ryan Sukmatama; Muhammad Ali Fikri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Good mental health is a state of well-being where individuals are able to cope with life's stresses, work productively, and contribute to their communities. In the workplace, good mental health promotes productivity and a positive work environment. Conversely, poor mental health can reduce performance and increase the risk of occupational hazards, especially in the health sector such as hospitals. This study aimed to identify the mental health of health workers in Yogyakarta using the Self-Reporting Questionnaire (SRQ-20). The research method used a descriptive survey involving 87 respondents who were given the SRQ-20 questionnaire. The results showed that 17.2% of the 87 respondents experienced mental emotional disorders, with the majority of symptoms being headaches, anxiety, and depression.